Electromagnetically generated extracorporeal shockwaves for fragmentation of extra-and intrahepatic bile duct stones: indications, success and problems during a 15 months clinical experience. Issue 2 (February 1990) - Staritz, M; Rambow, A; Grosse, A; Hurst, A; Floth, A; Mildenberger, P; Goebel, M; Junginger, T; Hohenfellner, R; Thelen, M
Abstract : Electromagnetically generated extracorporeal shock waves (without waterbath) were applied after intravenous premedication with 10-15 mg diazepam and 100 mg tramadol in the treatment of 33 patients (aged 32 to 91 years) with multiple intrahepatic stones (n = 4) or huge common bile duct stones (n = 29, 18-30 mm in diameter), which could not be removed by conventional endoscopy. Stone disintegration was achieved in 70% of common bile duct stones and in all intrahepatic concrements after 800-7500 discharges, which were applied during one (n = 21), two (n = 6) or three sessions (n = 6). Apart from mild fleabite-like petechiae at the side of shock wave transmission no other side effects were observed for a total of 51 procedures. We believe electromagnetically generated shock waves are safe, easy to apply, and relatively effective in the therapy of common bile duct and intrahepatic stones.